Numerical investigation and optimization of a novel hybrid solar chimney for air pollution mitigation and clean electricity generation. (25th May 2023) - Hachicha, Ahmed Amine; Abo-Zahhad, Essam M.; Oh, Sahuck; Issa, Salah; Rahman, S.M.A.
Highlights: A novel hybrid filter-equipped solar chimney collector is studied. Simulations are carried out to evaluate the performance of the hybrid system. Response surface method and multi-objective optimization are conducted. Optimum configuration of the filter-equipped solar chimney collector is determined. The system generates 28.3 kW of electricity at 90.5% of filter efficiency in UAE. Abstract: With the increasing energy demands and environmental concerns, more attention is paid to sustainable and renewable energy solutions. This work proposes a hybrid filter-equipped solar chimney power plant to purify the outdoor air and generate electricity simultaneously. A two-dimensional numerical model that incorporates the filter model, the turbine model, and a two-band radiation model is developed to study and optimize the performance of the novel system. Both chimney and filter models are validated with numerical and experimental data from the literature. The impact of the air filter on the thermal performance and fluid flow characteristics is investigated by varying the weather parameters. Moreover, multi-objective optimization of the filter position is carried out using response surface methodology. The findings indicated that placing the air filter closer to the collector inlet gives the best configuration. The results of a case study in Sharjah showed that the optimized hybrid filter-equipped solar chimney could produce around 28.3 kW of electricity while purifying the outdoor air at a rate of 447.6 m 3 /s. The proposed hybrid system has comparable capabilities to uncombined systems with only 6 % power reduction and less than 35 % of clean air at higher filter efficiency.